Diagnosis of mycobacterial skin infections. (2nd September 2019) - Kromer, Christian; Fabri, Mario; Schlapbach, Christoph; Schulze, Marco H.; Groß, Uwe; Schön, Michael P.; Buhl, Timo
Summary: The diagnosis of cutaneous mycobacterial infections may be challenging. Owing to the broad spectrum of their clinical presentations, mycobacterioses have to be considered as differential diagnoses to many inflammatory dermatoses. Diagnostic measures comprise histology including special staining, cultures and molecular microbiological examinations as well as the detection of cellular immune reactions of the patient by means of interferon‐γ release assays and skin testing. Clinicians should know the appropriate use and combination of procedures to diagnose mycobacterioses quickly and correctly and to avoid costs and delays caused by unnecessary examinations. This mini review summarizes advantages, limitations, and pitfalls of diagnostic methods for mycobacterial skin infections.